The Value of Contrast-Enhanced Ultrasound in the Evaluation of Carotid Web - Zhou, Qingqing; Li, Rui; Feng, Shuo; Qu, Fengling; Tao, Chunrong; Hu, Wei; Zhu, Yuyou; Liu, Xinfeng (Frontiers in Neurology, 2022)
Objectives The purpose of this study was to investigate whether contrast-enhanced ultrasound (CEUS) is more advantageous than conventional ultrasound in the diagnosis of carotid web (CaW) and to compare the clinical characteristics of patients in different age groups. Methods Seventeen patients admitted to the hospital from October 2019 to December 2021 were included in our study. Patients were initially diagnosed with CaW using digital subtraction angiography (DSA), and conventional ultrasound and CEUS were completed. Baseline patient data were analyzed and compared between the <60 years old CaW group and the ≥60 years old CaW group to explore the differences between the two groups. Then, comparing the accuracy of conventional ultrasound and CEUS. Results A total of 17 CaW patients participated in this study, including 4 female patients (23.5%) and 13 male patients (76.5%), with an average age of 59.41 (±10.86) years. There were 9 patients (52.9%) with left CaW and 8 patients (47.1%) with right CaW. Acute ischemic stroke (AIS) occurred in 14 patients (82.4%). Thrombosis occurred in five of 17 patients (29.4%). There was a significant statistical difference about the thrombosis between the <60 years old CaW group and the ≥60 years old CaW group [<60 years group: 0 (0%), ≥60 years group: 5 (62.5%), P = 0.005]. Seven patients (41.2%) received medical management, nine patients (52.9%) had carotid artery stenting (CAS), and one patient (5.9%) had carotid endarterectomy (CEA). None of the patients had recurrent stroke during the follow-up period. The diagnostic rate of CaW and thrombus by CEUS was higher than that by conventional ultrasound, and there was a significant statistical difference in the diagnosis of thrombus between CEUS and conventional ultrasound (χ2 = 4.286, P = 0.038). Conclusions CEUS may have a higher diagnostic accuracy for CaW with thrombosis, and it has a higher clinical application prospect.